(untitled) (National Administration Journal, 2019)
The objective of this article was to analyze the factors that make up a business management system, which enables to optimize the administration of human, material and financial resources at the disposal of organizations so that they can perform their activities. This essay is derived from a process, whose theoretical foundation is set into the conceptualization and contextualization of the management system, in the stages covered by the said system via proper use. The methodology is quantitative and the study method was centered on a case by means of information analysis through instruments such as SPSS software. Also, different stages were used, allowing field work to be carried out, as the type of research is descriptive. The main conclusion is that the results obtained in the advanced study were not encouraging. It is evident that today there is no homogeneity in the analyzed variables and this reveals the flaws contained within the company under study.